Bull fighter [videorecording (DVD)] - Martinez, Olivier, 1966-; Forbes, Michelle, 1965-; Serna, Assumpta, 1957-; Wahlberg, Donnie, 1969-; Cameron-Scorsese, Domenica; Parks, Michael, 1940-2017; Harris, Jared, 1961-; Dafoe, Willem; Schmidt, Rohn; Clarke, Vince (Screen Media Films ; Distributed by Universal Studios Home Video, 2005)
In this modern western, a shiftless drifter fascinated with bullfighting, is implicated in the accidental goring death of a crime boss' daughter and finds himself the unwitting target of a vicious manhunt.